An uncommon presentation of scalp sarcoidosis: window to systemic sarcoidosis - Kamble, Pramod; Gole, Prachi; Choithani, Payal; Mahajan, Sunanda (International Journal of Research in Dermatology, 2025)
Sarcoidosis is a multisystem disease with obscure etiology, slight female preponderance and mainly affects lungs, lymph nodes, skin and eyes. Cutaneous involvement is polymorphic, seen in 25-30% of patients and represents tip of an iceberg of systemic involvement. Scalp sarcoidosis though common, it rarely presents as sole manifestation. Though histopathology and reticulin staining serve as confirmatory, full body examination, pulmonary function test and blood examination including serum angiotensin converting enzyme and calcium levels, ophthalmological examination and tuberculosis testing is necessary. We present such an unusual case of scalp sarcoidosis which found to be a window to a systemic disease.